A combination of depression and liver Qi stagnation and spleen deficiency syndrome using a rat model. Issue 8 (30th April 2020) - Li, Xiao‐Juan; Qiu, Wen‐Qi; Da, Xiao‐Li; Hou, Ya‐Jing; Ma, Qing‐Yu; Wang, Ting‐Ye; Zhou, Xue‐Ming; Song, Ming; Bian, Qing‐Lai; Chen, Jia‐Xu
Abstract: A syndrome ( Zheng in Chinese) plays a critical role in disease identification, diagnosis, and treatment in traditional Chinese medicine (TCM). Clinically, the liver Qi stagnation and spleen deficiency syndrome (LQSSDS) is one of the most common syndrome patterns. Over the past few decades, several animal models have been developed to understand the potential mechanisms of LQSSDS, but until now, simulation of the syndrome is still unclear. Recently, several studies have confirmed that an animal model combining a disease and a syndrome is appropriate for simulating TCM syndromes. Overlapping previous studies have reported that depression is highly associated with LQSSDS; hence, we attempted to develop a rat model combining depression and LQSSDS. We exposed the rats to different durations of chronic unpredictable mild stress (CUMS). Subsequently, the evaluation indicators at macrolevel consisted of behavioral tests including open field test, sucrose preference test, and forced swim test, food intake, body weight, white adipose tissue, fecal water content, visceral hypersensitivity, and small bowel transit, and the evaluation indicators at microlevel included changes of hypothalamic–pituitary–adrenal axis. Serum D‐xylose absorption was used to comprehensively confirm and assess whether the model was successful during the CUMS‐induced process. The results showed that rats exposed to 6‐week CUMS procedure exhibited significantly similar traits to the phenotypes of LQSSDS and depression. This study provided a new rat model for the LQSSDS and could potentially lead to a better understanding of the pathophysiology of LQSSDS and the development of new drugs for this syndrome.